Government Policy Intervention Programmes in Ogun State: Youth Acceptability and Challenges (Global Journal of Human-Social Science, 2020)
Every government acknowledged to be proficient is always observed to be responsive to the needs of her citizenry particular ly the teaming population of her youth through series of intervention programmes. This study examined the available government intervention programme, its youths' acceptability of such programmes and some challenges encountered in the process. The study adopted the qualitative design using narrative approach with a population of 4,500 Voluntary Teachers Corps Scheme (VTCS) and 12 Desk Officers in the Teaching Service Commission of Ogun State. A sample of 60 VTCS and two (2) Desk Officers constituted the Focus Discussion Group. The selection process involved the multi stage, stratified, purposive, convenient and simple random sampling techniques. The data collected were analyzed using content analysis. The results showed that government intervention programmes were in different areas such as sports, education, job creation, r ural school study, agriculture and agro allied matters, works and services to mention a few.
Keywords: government intervention programme; youth; acceptability; challenges